Labor Market Reforms and Current Account Imbalances - Beggar-thy-Neighbor Policies in a Currency Union? - Timo Baas; Ansgar Belke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Member countries of the European Monetary Union (EMU) initiated wideranging labor market reforms in the last decade. This process is ongoing as countries that are faced with serious labor market imbalances perceive reforms as the fastest way to restore competitiveness within a currency union. This fosters fears among observers about a beggar-thy-neighbor policy that leaves non-reforming countries with a loss in competitiveness and an increase in foreign debt. Using a two-country, two-sector search and matching DSGE model, we analyze the impact of labor market reforms on the transmission of macroeconomic shocks in both, non-reforming and reforming countries. By analyzing the impact of reforms on foreign debt, we contribute to the debate on whether labor market reforms increase or reduce current account imbalances. – – In den letzten zehn Jahren begannen einzelne Mitgliedstaaten der EU, weitreichende Arbeitsmarktreformen durchzuführen. Dieser Prozess hält an, da Arbeitsmarktreformen als schnellster Weg wahrgenommen werden, die Wettbewerbsfähigkeit der Volkswirtschaft zu erhöhen und Arbeitsmarktungleichgewichte zu beseitigen. Von einigen Beobachtern wird diese Politik als "beggar-thy-neighbor" kritisiert, da die erhöhte Wettbewerbsfähigkeit zu Lasten der Handelspartner innerhalb der EU gehe, die Zahlungsbilanzungleichgewichte erhöhe und so die Auslandsverschuldung erhöhe. In diesem Artikel verwenden wir ein Zwei-Länder DSGE Modell mit Arbeitsmarktfriktionen, um die Wirkung von Arbeitsmarktreformen in dem Reform- wie auch dem Nichtreformland zu analysieren. Da wir insbesondere die Auswirkungen auf die Auslandsverschuldung berücksichtigen, tragen wir zur Debatte um die Wirkung von Arbeitsmarktreformen auf Zahlungsbilanzungleichgewichte innerhalb der Eurozone bei.
Keywords: E24; E32; J64; F32; 330; current account deficit; labor market reforms; DSGE models; search and matching labor market